Respostas

2014-05-22T21:24:42-03:00
- o quadrado da diferença => (x - 3)² = x² - 2.3.x + 3² = x² - 6x + 9
- igual a 5 vezes o número x, diminuído de 1 => 5x - 1, logo:
(x - 3)² = 5x - 1 => x² - 6x + 9 = 5x - 1 => x² - 6x - 5x + 9 + 1 = 0 =>
=> x² - 11x + 10 = 0, p/ a = 1 // b = -11 // c = 10
Δ = b² -4ac = (-11)² - 4.(1)(10) = 121 - 40 = 81
x' = (-b+√Δ)/2a = (11 + 9)/2 = 10
x" = (-b-√Δ)/2a = (11 - 9)/2 = 1
..............
P R O V A :
p/ x = 1 => (1)² - 11.(1) + 10 = 0 => 1 -11 +10 = 0 => 0 = 0
p/ x = 10 => (10)² - 11(10) + 10 =0 => 100 - 110 + 10 = 0 => 0 = 0
..............
As raízes da equação são (1, 10)

1 5 1